Pengaruh pemberian pupuk anorganik (NPK+Silikat) dengan dosis berbeda terhadap kepadatan Skeletonema costatum pada pembenihan udang windu - Fitriani; Fendi; Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2017)
Skeletonema costatum one type of phytoplankton commonly cultivated in the shrimp hatchery (Penaeus monodon Fabr.). Plankton S. costatum has a high nutrient content, small size is used as a natural feed of tiger shrimp larvae, especially in the zoea to mysis stadia. The aim of this research is to know the effect of inorganic fertilizer (NPK+Silicate) with dosage of 5 ppm, 15 ppm and 20 ppm to the density of S. costatum on tiger shrimp. The study was conducted for 2 weeks in July 2011 at UPTD Balai Benih Ikan Pantai Muna, Ghonebalano village, Duruka district, Muna regency, Southeast Sulawesi. The experiment used a 3-liter volume on stoples, a salinity water of 20 ppm. The study used Completely Randomized Design (RAL) with NPK and Silicate treated fertilizer with 5 ppm, 10 ppm (control), 15 ppm and 20 ppm with 3 replications. The initial density of S. costatum was 10,000 cells mL-1 per unit. The data were analyzed by ANOVA using IBM SPSS Statistic 22. The results showed that inorganic fertilizer application (NPK+Silicate) with different dose gave a very real effect on the density of S. costatum cells. Treatment of 15 ppm fertilizer dosage was significantly different with control and other treatment, average cell density was 121,000 cells mL-1. Based on cell growth, the 15 ppm fertilizer dosage has the best growth with an average cell increase of 1,2705 cells mL-1 day-1.